RETHINKING INSURANCE DISPUTES - Abdalyan, Ani M. (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2003)
All stakeholders in the insurance industry appreciate the critical importance of alternate dispute resolution (“ADR”) to the resolution of insurance disputes. What follows is a practical and in-depth analysis of negotiation, mediation, and arbitration as these dispute resolution methods relate to insurance. The author weaves in confidentiality, privilege, and ethics with a view to enhancing the effectiveness and efficiency of ADR in insurance disputes. This analysis serves as a foundation tool for ADR practitioners in the insurance industry and for future thoughts to follow.